Study on the problems faced by drivers and passengers on the one man operation bus service City Liner Sdn Bhd / Nor Zarina Ismail - Ismail, Nor Zarina (1996)
One-man operation bus service is a new system to the Malaysian. Before the implementation of the OMO system, passengers are relaxing boarding on bus without thinking to prepared the coins for bus fares. Bus drivers also did not need to faced the problem with the passengers especially to ensure passengers pay the fares because he had an assistant - the conductor to collect the fares from the passengers. This study had identified the problem faced by the drivers and the passengers on the implementation of the OMO system. Drivers had problems with their routine work as bus drivers. In OMO system drivers has extra job to do. He need to assist the passengers pay bus fares on the ticketing machine, need to drive safely and to ensure passengers board the bus safely. Passengers also need to prepare the enough coins if they do not lose their money according to the ticketing machine do not return the change money. From the observation and analysis made by the researchers, OMO bus service is a good service to be implemented but a little changes on the system might made the Cityliner OMO bus service much more better and efficient.